A Supramolecular Antibiotic Switch for Antibacterial Regulation. Issue 45 (26th August 2015) - Bai, Haotian; Yuan, Huanxiang; Nie, Chenyao; Wang, Bing; Lv, Fengting; Liu, Libing; Wang, Shu
Abstract A supramolecular antibiotic switch is described that can reversibly "turn‐on" and "turn‐off" its antibacterial activity on demand, providing a proof‐of‐concept for a way to regulate antibacterial activity of biotics. The switch relies on supramolecular assembly and disassembly of cationic poly(phenylene vinylene) derivative (PPV) with cucurbit[7]uril (CB[7]) to regulate their different interactions with bacteria. This simple but efficient strategy does not require any chemical modification on the active sites of the antibacterial agent, and could also regulate the antibacterial activity of classical antibiotics or photosensitizers in photodynamic therapy. This supramolecular antibiotic switch may be a successful strategy to fight bacterial infections and decrease the emergence of bacterial resistance to antibiotics from a long‐term point of view.